The Influence of Using Information Transfer Technique towards Students’ Reading Comprehension - Septa Aryanika (FKIP, Universitas Lakidende Unaaha, 2015)
In a process of teaching learning activity, teachers strive to create activities in class to make the students understand with the material that teachers give, when a book as a main source of knowledge in learning process, reading is an important process in teaching learning activity, many teachers try to apply technique to make students comprehend of what they read, and to make students interested in reading activity. In this paper the author introduces the technique known as information transfer. By first collecting different definitions of the term and then by explaining its application to English language teaching that can be used in teaching reading activity. Therefore, the present study was carried out to investigate the relationship between the use of information transfer and students’ reading comprehension, i.e. to determine whether or not making use of information transfer has any influence on the students’ reading comprehension. The methodology was true-experimental design with the treatment. The population of this research was the second semester of the tenth grade students of MAN I Metro, Lampung. The sample taken was two classes randomly, 1K2 (X-2) and 1K3 (X-3) which consisted of 64 students. In collecting the data, the writer used the instruments in multiple-choice questions of descriptive text. After being tried-out, the instrument was used for the pre-test and the post-test.